TOP-Plus Is a Versatile Biosensor Platform for Monitoring SARS-CoV-2 Antibody Durability. (29th April 2021) - Racine-Brzostek, Sabrina E; Karbaschi, Mohsen; Gaebler, Christian; Klasse, P J; Yee, Jim; Caskey, Marina; Yang, He S; Hao, Ying; Sukhu, Ashley; Rand, Sophie; Chadburn, Amy; Shi, Yuanyuan; et al.
Abstract: Background: Low initial severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody titers dropping to undetectable levels within months after infection have raised concerns about long-term immunity. Both the antibody levels and the avidity of the antibody–antigen interaction should be examined to understand the quality of the antibody response. Methods: A testing-on-a-probe "plus" panel (TOP-Plus) was developed to include a newly developed avidity assay built into the previously described SARS-CoV-2 TOP assays that measured total antibody (TAb), surrogate neutralizing antibody (SNAb), IgM, and IgG on a versatile biosensor platform. TAb and SNAb levels were compared with avidity in previously infected individuals at 1.3 and 6.2 months after infection in paired samples from 80 patients with coronavirus disease 2019 (COVID-19). Sera from individuals vaccinated for SARS-CoV-2 were also evaluated for antibody avidity. Results: The newly designed avidity assay in this TOP panel correlated well with a reference Bio-Layer Interferometry avidity assay ( r  =   0.88). The imprecision of the TOP avidity assay was <10%. Although TAb and neutralization activity (by SNAb) decreased between 1.3 and 6.2 months after infection, the antibody avidity increased significantly ( P  <   0.0001). Antibody avidity in 10 SARS-CoV-2 vaccinated individuals (median: 28 days after vaccination) was comparable to the measured antibody avidity in infected individuals (median: 26 days after infection). Conclusions: This highly precise and versatile TOP-Plus panel with the ability to measure SARS-CoV-2 TAb, SNAb, IgG, and IgM antibody levels and avidity of individual sera on one sensor can become a valuable asset in monitoring not only patients infected with SARS-CoV-2 but also the status of individuals' COVID-19 vaccination response.